Genetic Association Between Epigenetic Aging-Acceleration and the Progression of Mild Cognitive Impairment to Alzheimer's Disease. Issue 9 (7th July 2022) - Liu, Hongliang; Lutz, Michael; Luo, Sheng; ,
Abstract: Alzheimer's disease (AD) is a progressive neurodegenerative disorder, and previous studies have shown its association with accelerated aging. In this study, we hypothesized that single nucleotide polymorphisms (SNPs) that contributed to aging acceleration are also associated with the progression from mild cognitive impairment (MCI) to AD. By applying genetic correlation analysis and single-locus survival analysis, we investigated the associations between intrinsic- and extrinsic-epigenetic-age-acceleration (IEAA and EEAA) related SNPs and the progression time from MCI to AD dementia using the data of 767 MCI participants from the Alzheimer's Disease Neuroimaging Initiative (ADNI) study and 1 373 MCI patients from the National Alzheimer's Coordinating Center (NACC) study. Genetic correlations were found between IEAA/EEAA and AD (positive for IEAA-AD and negative for EEAA-AD). We revealed that 70 IEAA and 81 EEAA SNPs had associations with the progression time from MCI to AD with Bayesian false-discovery probability ≤ 0.8 in the ADNI study, with 22 IEAA SNPs and 16 EEAA SNPs being replicated in the NACC study ( p < .05). Polygenic risk score (PRS) analysis showed that EEAA PRS but not IEAA PRS was associated with AD progression and the trend of decreasing fusiform gyrus volume in 2 data sets. Risk models incorporating both EAA PRSs did not show any significant improvement in predictive accuracy. Our results revealed multiple genetic variants with pleiotropic effects on both EAA and AD, which suggested shared genetic architecture between epigenetic age acceleration and AD progression.